How is coffee competitive for entrepreneurship in the rural tourism industry: Probability perspectives - Muh. Fahrurrozi; Basri, Hasan; Muhamad Ali; Cahyono, Heru; Rindrayani, Sulastri Rini; Hanapi; Ramli, Muhammad (Kasetsart Journal of Social Sciences, 2026)
This study examines the structure and competition of the ecosystem of the eastern Lombok regency coffee industry in Indonesia, with a particular focus on the intersection of tourism growth and the local coffee landscape. When a problem arises, coffee is explained in the context of one of the important monetary cultures of Indonesia, which, due to its rich biodiversity and suitable climatic conditions, has a high potential for coffee production. The research problem of this study is to understand the factors that contribute more to the positive strengthening of the competitiveness of coffee in the region. The study used a qualitative approach in which coffee growers and business owners, as well as members of the community, used a semi-structured interview method to obtain a lot of information based on their experiences and views. This study found evidence to support the notion that the cultural aspects of coffee drinking, which are inherent in both this region and its geography, are important in building a strong coffee industry in the country. It was concluded that improving the quality of coffee and taking advantage of opportunities related to the development of tourism can benefit the local economy while responding to the growing demand for Indonesian coffee both domestically and internationally. As this study shows, key players, including local authorities and coffee producing companies, should support quality improvement programs to get the most out of the high demand for coffee around the world, ultimately making Eastern Lombok a fierce competitor in the coffee market.